Bottle Tongue Entrapment: Increasingly Popular Soda Becomes Airway Emergency. Issue 9 (September 2018) - Long, Michael T.; Murray, Matthew P.
Abstract : Abstract: Tongue entrapments within bottles are very rare childhood mishaps. The most immediate hazard in a tongue entrapment is airway obstruction. Tongue entrapment is an airway emergency; contingency planning to maintain airway patency, oxygenation, and ventilation is critical. Here, we report the case of a 5-year-old girl presenting to a pediatric emergency department with an increasingly popular novelty soda bottle, featuring a unique and dangerous design, entrapped on her tongue. Operative removal was anticipated. Although initially stable, she became agitated and developed retching while awaiting transfer to the operating room. Symptoms were managed medically after careful consideration of the risks and benefits of drug adverse effects while airway contingencies were planned. Fortunately, airway interventions were not necessary in the emergency department. The child was transferred to and intubated in the operating room where the bottle was removed uneventfully. This case demonstrates our approach to an evolving difficult airway in our pediatric emergency department. We review the available literature on similar presentations.